DESKRIPSI KARAKTER MORFOLOGI UBI KAYU (Manihot esculenta Crantz) JURAY DARI KABUPATEN ROKAN HULU - Murtiana Caniago; Dewi Indriyani Roslim; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cassava is an alternative food to substitute rice as a staple food. The improvement of cassava in breeding program requires many high genetic diversity of cassava. The objective of this study was to describe the morphological characters of cassava cv. Juray from Kabupaten Rokan Hulu, Riau. This research was conducted at Biology Department, FMIPA UR, for 12 months, started from March 2013 to February 2014. The cassava stems were planted and then observed on fifth and twelfth months. The results showed that cassava cv. Juray had morphological characters as follows: the stem color was grey, the stem diameter was large (3.4 cm), the stem texture was grooved, the petiole length was medium (9.77), the flowering time was 10 months after planting, the tuber shape was irregular, the external color of tuber was light brown, the tuber cortex thickness was thin (1 mm), the tuber cortex color was cream, and the root pulp color was white.